Peran Komitmen Kerja dan Kepuasan Kerja dalam Kinerja Pegawai PT. Bank Sulselbar Cabang Barru - S, Praweldi; Nur, Irawati; Nurnaningsih, Nurnaningsih; Jusnia, Jusnia (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
The purpose of this study was to determine the effect of work commitment and job satisfaction partially and simultaneously on the performance of employees of PT. BANK SULSELBAR BRANCH BARRU. The analytical methods used in this research are observation, interviews, questionnaires, documentation, and library research. Determination of the sample was determined by saturated sampling (census) and obtained as many as 41 respondents. The results of this study indicate that (1) Partially Work Commitment has a positive and significant effect on employee performance at PT. Bank Sulselbar Barru Branch. This is indicated by the value of the results of the t test analysis obtained by t count > t table, namely 4.782 > 2.024 and a significance value of 0.004 (< 0.05). And partially Job Satisfaction has a positive and significant effect on employee performance. This is indicated by the value of the results of the t test analysis obtained by t count > t table, namely 4,768 > 2.024 and a significance value of 0.000 (<0.05). (2) Simultaneously Work Commitment and Job Satisfaction have a positive and significant effect on employee performance. This is indicated by the value of the results of the F test analysis obtained by the value of F count > F table, namely 29,941 > 3.24 with a significant level of 0.000 <0.05. These results indicate that the second hypothesis is accepted. (3) The results of the determination coefficient of 0.737 indicate the ability of the independent variable to affect the dependent variable, namely 73.7%, therefore for researchers who will research with the same theme, it is advisable to add other variables that are not yet present in this study or to examine other variables , so that research results can be even better and prove the hypothesis. It is possible that this will provide results of a comparison of the effects of previous studies.